Feeding ecology of elasmobranch fishes in coastal waters of the Colombian Eastern Tropical Pacific - Mejía-Falla Paola A; Navia Andrés F; Giraldo Alan (BMC Ecology, 2007)
Abstract Background Stomach contents of 131 specimens of five elasmobranch species (Mustelus lunulatus, Dasyatis longa, Rhinobatos leucorhynchus, Raja velezi and Zapteryx xyster) caught in the central fishing zone in the Pacific Ocean of Colombia were counted and weighed to describe feeding habits and dietary overlaps. Results Twenty-one prey items belonging to four major groups (stomatopods, decapods, mollusks and fish) were identified. Decapod crustaceans were the most abundant prey found in stomachs. The mantis shrimp Squilla panamensis was the main prey item in the diet of M. lunulatus; tiger shrimp Trachypenaeus sp. was the main prey item in the diet of Rhinobatos leucorhynchus and Raja velezi, and Penaeidae shrimp were the main prey items in the diet of Z. xyster. Furthermore, fish were important in the diet of Raja velezi, Z. xyster and D. longa. The greatest diet breadth corresponded to Z. xyster whereas M. lunulatus was the most specialized predator. Finally, four significant diet overlaps between the five species were found, attributable mainly to Squillidae, Penaeidae and Fish. Conclusion Shrimps (Penaeidae and stomatopods) and benthic fishes were the most important food types in the diet of the elasmobranch species studied. Diet breadth and overlap were relatively low. Determination of food resource partitioning among the batoid species studied was not possible. However, we identified partitions in other niche axes (time of feeding activity and habitat utilization). It is possible to assume that diffuse competition could be exceeding the biunivocal competition among the studied species. Therefore, this assemblage would have a strong tendency to trophic guild formation.